Dynamic relationship between international tourism, economic growth and environmental pollution in the OECD countries: evidence from panel VAR model. Issue 1 (31st December 2022) - Gedikli, Ayfer; Erdoğan, Seyfettin; Çevik, Emrah Ismail; Çevik, Emre; Castanho, Rui Alexandre; Couto, Gualter
Abstract: The aim of this study is to examine the impact of international tourism on economic growth and carbon emissions by using the Panel VAR model in selected OECD countries. By using yearly data for the periods of 1995 and 2020, we examine the dynamic relationship between international tourism, economic growth, and carbon emissions using the Granger causality test and impulse responses analysis. Although we could not determine the presence of a causal link between the variables using the Granger causality test, impulse responses analysis confirmed that responses of carbon emissions and economic growth to an unexpected international tourism shock are positive and significant. On the other hand, impulse responses analysis results show that responses of carbon emissions and economic growth to unexpected international tourism are positive and significant. The empirical findings also indicated that the responses of carbon emissions to an unexpected international tourism shock are higher than the responses of economic growth to an unexpected international tourism shock and these findings indicate that the negative impact of international tourism on environmental quality is greater than its positive impact on economic growth. Policymakers should take actions and measures to reduce the impact of international tourism on environmental deterioration. Improvements and dissemination of eco-friendly technologies in all tourism activities may help to reduce the negative impact of international tourism on carbon emissions.